The Management of Corporate Culture in Entrepreneurial Firms - Flamholtz, Eric G.; Randle, Yvonne (Senate Hall, 2009)
It has been recognized that corporate culture is of critical importance to organizational success. For some companies, a strong positive culture is a true "asset." For others, their corporate culture is a true economic "liability." Given its role in organizational success and failure, scholars and practicing managers must understand the nature, functioning, evolution and management of corporate culture, especially in entrepreneurial firms. Although the importance of culture has been recognized, a systematic framework for its management has remained elusive. This article takes steps towards this objective. It addresses several key issues: What is "corporate culture"? Why is it important? How does culture manifest itself in organizations? What are the different "types" of cultures? What are the key aspects of corporate culture? How is created in entrepreneurial companies? How does culture evolve, "mutate" or change? What are some of the special cultural challenges facing entrepreneurial firms? How can corporate culture be managed? Keywords: corporate culture; culture management; key cultural dimensions; entrepreneurial culture transformation crisis.
Keywords: corporate culture|culture management|key cultural dimensions|entrepreneurial culture transformation crisis